Synthesis And Fabrication Of Drop-Coated Sn02 Thick Film Sensor Via Sol Gel Method For Ethanol Gas Detection - Low, Kok Wei (Universiti Sains Malaysia, 2017)
Tin dioxide (SnO2) nanopowders has been successfully synthesized via sol-gel method by dissolving the precursor, tin (IV) chloride pentahydrate in distilled water and adding ammonia solution afterwards; in which the methods are relatively simpler and cheaper. The obtained ethanol sensing materials were then characterized with X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) and Brannauer-Emmett-Teller (BET) analysis. From the XRD result, the crystallite sizes increase with the rise in calcination temperature; where the crystallite size obtained at calcination temperature of 400 oC, 500 oC and 600 oC are 11.28 nm, 13.06 nm and 18.17 nm respectively. SEM characterization shows homogenous distribution of SnO2 nanoparticles and hints agglomeration at higher calcination temperature. It was found through EDX analysis that the chemical composition of the SnOx synthesized is confirmed to be SnO2. After that, the synthesized SnO2 powders were deposited on alumina substrates through drop coating method for sensor fabrication. To understand the effect of film thickness on the sensitivity, the sensors were fabricated at 3, 5 and 7 drop layers of sensing materials. Operating temperature ranging from 200 oC to 400 oC and different ethanol gas concentrations (200 ppm to 1000 ppm) were also used for sensor testing to study the gas sensing behavior at different conditions. It was found that the as-prepared SnO2 sensors work best at 300 oC and the sensitivity of the sensors exhibits linear dependency on the ethanol gas concentration. In all, the sensor that showed highest sensitivity to ethanol gas was the one fabricated using 5 drop layers of SnO2 nanopowders calcined at 500 oC. This sensor also outperformed the sensor fabricated with commercial SnO2 nanopowders by having a higher sensitivity, ascribed y the former having smaller crystallite size and higher surface area. From the XRD and BET analysis, the commercial SnO2 powder is 70.64 nm in size and have an average surface area of 4.55 m2/g whereas the best synthesized SnO2 powder is only 13.06 nm in size and have a higher average surface area of 36.74 m2/g.